Design, Fabrication And Testing Of A Solid Propellant Rocket Motor - Ang , Kiang Long (2011)
The objectives of this paper are to design, fabricate and test a solid propellant rocket motor. First, Literature studies on rocket motor fundamental which covered existing motor designs and theories for determining the properties of the rocket motor. Next, the numerical analysis in grain material and dimension for the rocket motor are included in this report. The simulation result by computer aids software (SolidWorks 2008) for the flow characteristics especially in the nozzle area is presented. The fabrication techniques and the Non Destructive Test (NDT) on solid propellant also included in this thesis. Two solid propellant grain configurations were designed in this project to studies their effect on the rocket performance.